2006
DOI: 10.1177/0148607106030002115
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of a Soybean Oil Emulsion on Human Lymphocytes and Neutrophils

Abstract: Soybean oil emulsion given as a single dose of 500 mL promotes lymphocyte and neutrophil death that may enhance the susceptibility of the patients to infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 69 publications
0
41
1
1
Order By: Relevance
“…Cury-Boaventura et al (36) observed a decrease in the proliferation of lymphocytes from volunteers who received a lipid emulsion rich in LA. This effect was possibly attributable to the toxicity of the LA, whose plasma level was markedly increased.…”
Section: Discussionmentioning
confidence: 98%
“…Cury-Boaventura et al (36) observed a decrease in the proliferation of lymphocytes from volunteers who received a lipid emulsion rich in LA. This effect was possibly attributable to the toxicity of the LA, whose plasma level was markedly increased.…”
Section: Discussionmentioning
confidence: 98%
“…The time required for their incorporation is very short. In fact, some studies have shown modification in fatty acids plasma membranes composition immediately after lipid emulsion infusion (Cury-Boaventura et al, 2006). More recently, our group demonstrated that 5 days of pure linoleic acid supplementation increases the percentage of linoleic acid, without altering oleic and arachidonic acids contentes, in rat neutrophil membranes (Rodrigues et al, 2010).…”
Section: Omega 6 (N-6) Fatty Acidsmentioning
confidence: 90%
“…In the present study, OA and LA at 25 mM raised the stimulatory effect of IL-2 on lymphocyte proliferation. Considering the fact that high concentrations of these FA induce apoptosis in various cell types, 58,59 it is suggested that OA and LA might modulate signal transduction to enhance lymphocyte proliferation at low and non-toxic concentrations, whereas higher concentrations cause apoptosis. IL-2 signalling includes STAT5a/b, ERK 1/2 and Akt activation.…”
Section: Discussionmentioning
confidence: 99%